Active Flow Control II Papers Contributed to the Conference "Active Flow Control II 2010", Berlin, Germany, May 26 to 28, 2010 - King, Rudibert (Notes on Numerical Fluid Mechanics and Multidisciplinary Design,, 2010)
This volume presents an updated and well balanced combination of theoretical and experimental state-of-the-art results of ACTIVE FLOW CONTROL. It combines new developments optimal open- and closed-loop control and model reduction for control. Numerical and experimental applications are considered from aeronautics, ground-based vehicles, turbo-machinery and combustors. The contributions to this book were presented at the Conference ACTIVE FLOW CONTROL II, held May 26-28, 2010, at the Technische Universität Berlin, Germany.